321. Eleven-year Case Series of the Anatomy and Microbiology of Musculoskeletal Infections in People who Inject Drugs. (31st December 2020) - Schade, Meredith A; London, Abby; Lin, Dan
Abstract: Background: Complex musculoskeletal infections(MSKI) can be seen in injection drug users. The objective of the study was to describe the anatomic location and microbial etiology of MSKI. Methods: This is a single center, eleven-year case series of adult patients admitted with infection of the musculoskeletal system from January 1, 2008 to December 31, 2018. Diagnosis codes for MSKI were used. As there are no diagnosis codes that specifically identify injection drug use, ICD-9 and ICD-10 codes for related diagnoses were used. The codes included opioid use disorder, drug abuse, heroin use, drug overdose, cocaine use, and methamphetamine use.Charts were then carefully reviewed to determine if a MSKI related to IDU had occurred. Fisher's exact test was used to calculate P values. Results: A total of 849 individual medical records were identified. Eighty-six distinct episodes of infection were found in eighty-two patients. Most patients were white, non-Hispanic, male, 50 years of age or younger. Tobacco use disorder(87.8%) and hepatitis C(64.6%) were common. Mental health disorders were identified in one third. The axial skeleton was involved in 61.6% and the appendicular in 25.6%. Soft tissue infection alone was present in 9%. Bacterial infections predominated with Staphylococcus aureus most frequent(67.4%) followed by Pseudomonas aeruginosa (11.6%). Candida species were uncommon. All soft tissue infections were polymicrobial. Infections of the appendicular skeleton were managed with antibiotics and surgery whereas infections of the axial skeleton were more likely to receive antibiotics alone. Seventy two percent had successfully completed treatment at one year. The remainder had relapsed due to same infection, died or were lost to follow up. Demographics of Study Population Anatomy and Microbiology of MSKI in PWID and 1-year Treatment Outcomes Anatomy and Microbiology of MSKI in PWID with Different Treatment Modalities Conclusion: MSKI in PWID continue to be found in younger persons with relatively few comorbidities. The infections predominantly involve the axial skeleton and are caused most often by Staphylococcus aureus . Gram-negative infections also occur and are due to environmental bacteria. Spinal infections were managed medically whereas infections of peripheral joints were also managed with surgery. An unfortunate number had relapse of infection, died or were lost to follow-up at 1 year, demonstrating the challenges of managing MSKI in this unique population Disclosures: All Authors : No reported disclosures